Effect of fly ash and bottom ash application as mix growing media on heavy metals status in vegetables - Putri, Anita Hazimah; Agusta, Herdhata; Bintoro Djoefrie , Mochamad Hasjim; Santosa , Edi (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2023)
Coal fly ash-bottom ash (FABA) is still possible to be used directly as a mixture of soil with other growing media in small-scale agriculture. This study aimed to determine and to identify the level of safety for the consumption of vegetable crops related to the adsorption of heavy metals due to the use of mixed FABA planting media. In this study, the proportion mixture of 6% FABA, 6% compost, and 8.6% fine coal (lignite) was applicated. The proportion ratio between FABA and soil was 1:15. The FABA media application was prepared for eggplant, chili, water spinach, spinach, mustard greens, and moringa vegetables. The study was conducted without any control treatment without FABA on the same soil type. As an alternative control, vegetables from local farmers, local markets, and supermarkets surrounding the study site were taken. The experimental results showed that the application of FABA did not increase nitrate and heavy metals content in vegetables. It can be concluded that vegetables grown on FABA media were safe and suitable for consumption in terms of acceptable daily intake of nitrate and various heavy metals, except for As intake in water spinach and mustard greens, which were recommended to be confirmed in further determination research.